Efficiency, Inefficiency and the MENA Frontier - Dimitris Christopoulos; Peter McAdam (European Central Bank (ECB), 2015)
In a stochastic frontier setting, we examine technical efficiency in the Middle East and North Africa (MENA). Evidence suggests that in addition to economic indicators, political and social ones play a key role in development and frontier technical efficiency profiles. The MENA have been characterized by increasing economic efficiency over time but with marked polarization. The paper analyses and nest many key hypotheses in the literature e.g., the contributions of religion, of natural resources, demographic pressures, human capital etc. The originality of our contribution is the use of a large data set (including principal components), and extensive robustness checks. The paper should set a comprehensive benchmark and cross check for related studies of development technical efficiency.
Keywords: C33; C38; C55; D24; E23; O11; 330; development; frontier efficiency; MENA; stochastic frontier